Differences of Corneal Biomechanics Among Thin Normal Cornea, Forme-Fruste Keratoconus, and Cornea After SMILE - Zhang, Di; Tian, Lei; Zhang, Haixia; Zheng, Yan; Fu, Caiyun; Zhai, Changbin; Jie, Ying; Li, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Background: To compare the corneal biomechanics of thin normal cornea (TNC) with thinnest corneal thickness (TCT) (≤500 µm), forme-fruste keratoconus (FFKC) and cornea after small incision lenticule extraction (Post-SMILE) had their central corneal thickness (CCT) matched by Corneal Visualization Scheimpflug Technology (Corvis ST). Methods: CCT were matched in 23 eyes with FFKC, 23 eyes by SMILE in 3 months post-operatively, and 23 TNC eyes. The differences in corneal biomechanics by Corvis ST among the three groups were compared. Results: There was no significant difference in CCT among the three groups, and the biomechanically corrected intraocular pressure (bIOP) did not differ significantly among the three groups (all p>0.05). There were significant differences in most DCR parameters between pre- and post-operatively (all p<0.05). Compared with TNC, the values of corneal deflection amplitude during the first applanation (A1DA), length at the first applanation (A1L), corneal deflection amplitude during the second applanation (A2DA), and maximum deformation amplitude (DA) decreased in 3 months after SMILE (all p<0.05), these values increased in the FFKC (all p<0.05). Conclusion: The majority of the DCR parameters were different among the three groups. The parameters A1DA, A1L, A2DA, and DA may be different between TNC and Post-SMILE, TNC and FFKC, and Post-SMILE and FFKC. Keywords: thin normal cornea, FFKC, Post-SMILE, corneal biomechanicans, Corvis ST